Experimental characterization of compact fluorescent lamps for harmonic analysis of power distribution systems - Andrés C. Henao-Muñoz (Universidad Nacional de Colombia) (Instituto Tecnológico Metropolitano, 2018)
The modeling of a compact fluorescent lamp for harmonic analysis under terminal voltage variation is presented in this paper. The compact fluorescent lamp is represented with the diode bridge rectifier model, which is commonly used for harmonic analysis. The set of parameters is estimated for different values of the terminal voltage applied to the lamp. The equations to estimate the parameters and the required measurements to calculate them are presented. To characterize the lamp an experiment is carried out varying the RMS terminal voltage from 10 V to 131.6 V and for each terminal voltage value the apparent, real and reactive powers, the power factor, the current and the applied voltage are registered. To validate the model in the range of the terminal voltage, the total harmonic distortion of current calculated with the experimental signal and the total harmonic distortion of current calculated with simulation software are compared. The results show that the compact fluorescent lamp can be represented for one set of parameters in the operation range of the terminal voltage suggested by the manufacture.